Parkinsons disease in occupational exposure to joss paper, a report of two cases - Chew, N.K.; Lee, M.K.; Ali, M.; Tan, C.T. (2003)
We report two genetically unrelated ethnic Chinese women, aged 63 and 60 years, who developed Parkinsons disease at the age of 55 and 53 years respectively. Both cases were working in the same joss paper shop for 15 years prior to the onset of Parkinsons disease. There was no family history of Parkinsons disease and exposure to other chemical or toxic agents. Biochemical analysis of joss papers revealed the presence of heavy metals such as lead, copper, zinc, and mercury, which has been implicated in the pathogenesis of Parkinsons disease. The Parkinsons disease in these two cases was attributed to occupational exposure to joss paper. Joss paper has not been associated with the development of Parkinsons disease previously.